Textbook Evaluation: A Framework for Evaluating the English Subject in Kurikulum Merdeka for the Tenth Grade - Suyadi Suyadi; Siti Aisyah (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This research is aimed at finding out the significance or not the significance of English textbooks under Kurikulum Merdeka be implemented at schools. It is widely accepted that a textbook is an essential component of the English as a Foreign Language classroom. Evaluation of a textbook, therefore, is of utmost importance so that its pedagogical contribution to the teaching and learning process can be assured. In the context of Kurikulum Merdeka in Indonesia, textbook evaluation is an even more important issue given the recent implementation of Senior High School students. Can the newly written curriculum textbook help teachers deliver the new curriculum objectives?. There is a lack of empirical studies showing how curriculum fitness can be evaluated. In addition, despite the repeated emphasis on the benefits of a post-use textbook evaluation by a number of researchers, relevant empirical studies, however, seem to lack much of the available literature is biased towards pre-use evaluation. By conducting this research, the researcher hopes the results can reveal the actual situation of English textbooks at Senior High Schools and whether or not, the textbook is implemented totally as it is or should be added or lessened of some materials in the textbook.